2014
DOI: 10.1530/eje-14-0098
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length analysis in Cushing's syndrome

Abstract: Introduction: Hypercortisolism in Cushing's syndrome (CS) is associated with increased morbidity and mortality. Hypercortisolism also occurs in chronic depressive disorders and stress, where telomere length (TL) is shorter than in controls. We hypothesized that shortening of telomere might occur in CS and contribute to premature aging and morbidity. Aim: To investigate TL in CS patients compared with controls. Methods: Seventy-seven CS patients (14 males, 59 pituitary, 17 adrenal, and one ectopic; 21 with acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…Our study builds on these findings by establishing a longitudinal relationship, because cortisol responsivity predicted telomere shortening over time. The results are also consistent with longitudinal clinical studies indicating that telomere length is shorter during active Cushing’s syndrome than when patients are in remission ( 34 ).…”
Section: Discussionsupporting
confidence: 88%
“…Our study builds on these findings by establishing a longitudinal relationship, because cortisol responsivity predicted telomere shortening over time. The results are also consistent with longitudinal clinical studies indicating that telomere length is shorter during active Cushing’s syndrome than when patients are in remission ( 34 ).…”
Section: Discussionsupporting
confidence: 88%
“…Leukocyte telomere length associations with resting cortisol concentrations are less clear, with reports of an inverse correlation (Epel et al, 2006) and of no significant correlation (Parks et al, 2009). In Cushing’s syndrome, LTL and cortisol levels were not significantly related cross-sectionally, but LTL significantly lengthened after remission from the active disease (Aulinas et al, 2013a; Aulinas et al, 2014; Aulinas et al, 2013b). Studies are more, but not always, consistent in showing inverse relationships between LTL and dynamic aspects of cortisol secretion (e.g., waking-associated increases in cortisol or cortisol responses provoked by psychological stress) (Gotlib et al, 2014; Kroenke et al, 2011; Revesz et al, 2013; Tomiyama et al, 2012) as opposed to basal, resting or even circadian cortisol levels.…”
Section: Potential Mediators Of Telomere Shortening In Psychiatricmentioning
confidence: 87%
“…Most studies on TL have been performed in healthy subjects, T2DM, cardiovascular disease or psychiatric conditions. We recently reported no differences in TL in a cross-sectional comparison of CS and controls, but when patients with active CS were evaluated longitudinally after biochemical control, telomere lengthening was observed despite being on average 3 years older [ 16 ]. However, no study has reported data on TL in CS related to metabolic or inflammatory state.…”
Section: Introductionmentioning
confidence: 99%